Paradigm shift: should the elderly undergo propofol sedation for DBE? A prospective cohort study. Issue 3 (23rd September 2017) - Ching, Hey-Long; Branchi, Federica; Sanders, David S; Turnbull, David; Sidhu, Reena
Abstract : Objective: Evaluate the safety of propofol-assisted double balloon enteroscopy (DBE) in elderly patients against a younger cohort. Design: Prospective cohort study Setting: All patients undergoing DBE over a 30-month period were recruited at our tertiary centre. Patients: 215 procedures in 161 patients were performed. An age cut-off of 65 years and above was used to define those who were elderly. Interventions: Patients were subcategorised into four groups: elderly or young undergoing DBE with propofol or conventional sedation (with midazolam±fentanyl). Main outcome measures: Patient demographics, comorbidities, procedural data, complications, diagnostic and therapeutic yield were compared. Results: Cardiovascular disease and a higher American Society of Anaethesiologists (ASA) status were more prevalent in elderly patients undergoing DBE with propofol (p<0.05). Common indications for DBE were occult and overt obscure gastrointestinal bleeding and suspected Crohn's disease (elderly vs young: 50.7% vs 42.3%, 17.8% vs 12% and 19.2% vs 26.1%, respectively). Diagnostic yield was higher in elderly compared with young patients (75.3% vs 58.5%, p=0.016). The most common findings in elderly and young patients were angioectasia (30.1% and. 18.3%, respectively) and ulcers (17.8% and 9.2%, respectively), while therapeutic intervention rates were comparable (42.5% vs 32.4%, p=0.18). ASA status did not affect propofol dose (p=0.55) or procedure duration (p=0.31). Tolerance scores were favourable in those receiving propofol compared with conventional sedation (p<0.05). There was no difference in complications between the four groups (p=0.17). Conclusion: Compared with young patients, propofol-assisted DBE in the elderly is safe and has a high diagnostic yield.